Developmental delay in a resource-constrained environment: An approach to early intervention - Pragashnie Govender; Vasantha Govender; Deshini Naidoo (South African Family Practice)
With a reduction in mortality rates of children under 5 years, in low- and middle-income countries, the responsibility to provide quality care to the increased number of surviving children becomes essential. Many of these children present with developmental delay and the onus inevitably rest on the healthcare system. There is, therefore, the need for recognising timely intervention as routine care for these children, who may have potential for a better quality of life with intervention. The authors advocate for early referral and intervention, and provide a brief overview of a holistic approach to developmental delay in low resourced settings from their perspective.